(untitled) (Open Herald: Periodical of Methodical Research, 2026)
Dental fluorosis is a developmental disorder of enamel caused by excessive fluoride intake during the period of amelogenesis. Despite the well-established cariostatic benefits of fluoride, its chronic overexposure leads to structural and aesthetic alterations in enamel. The aim of this study was to analyze the etiological factors and pathogenetic mechanisms underlying dental fluorosis as a pathology of hard dental tissues formed during tooth development. A narrative review of contemporary literature was conducted using major scientific databases. The results demonstrate that fluorosis is a dose- and time-dependent condition associated with ameloblast dysfunction, impaired protein degradation, and defective mineralization. The severity of enamel damage varies from mild opacities to severe hypomineralization with structural breakdown. Understanding the mechanisms of fluorosis is essential for prevention, early diagnosis, and rational management of this condition.